2017
DOI: 10.3389/fpsyg.2017.02033
|View full text |Cite|
|
Sign up to set email alerts
|

Stimulating the Right Temporoparietal Junction with tDCS Decreases Deception in Moral Hypocrisy and Unfairness

Abstract: Self-centered and other-regarding concerns play important roles in decisions of deception. To investigate how these two motivations affect deception in fairness related moral hypocrisy, we modulated the brain activity in the right temporoparietal junction (rTPJ), the key region for decision making involved in self-centered and other-regarding concerns. After receiving brain stimulation with transcranial direct current stimulation (tDCS), participants finished a modified dictator game. In the game, they played … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 45 publications
0
19
0
Order By: Relevance
“…Consequently, behavioral preference varied as a function of the sensitivity to physical pain of the victim across conditions. While follow-up research is needed to determine which interpretation is more appropriate, both of them are in line with the finding that activating the rTPJ decreases antisocial behavior (e.g., deception) (see Tang et al, 2017).…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…Consequently, behavioral preference varied as a function of the sensitivity to physical pain of the victim across conditions. While follow-up research is needed to determine which interpretation is more appropriate, both of them are in line with the finding that activating the rTPJ decreases antisocial behavior (e.g., deception) (see Tang et al, 2017).…”
Section: Discussionmentioning
confidence: 72%
“…Both electrodes were positioned firmly on the scalp with a plastic headband. The electrode montage and tDCS parameters were identical to those that successfully modulated cortical excitability of the rTPJ in previous studies (Jurcak et al, 2007;Santiesteban et al, 2012;Tang et al, 2017).…”
Section: Experimental Design and Statistical Analysismentioning
confidence: 71%
“…Under the active HD-tDCS condition, a relatively weak current (1.5 mA) was delivered for 20 min. For sham stimulation, a 1.5 mA current stimulus was delivered and lasted only 30 s consistent with previous research (Civai et al, 2015 ; Mai et al, 2016 ; Tang et al, 2017 ). For all three stimulation conditions, the stimulation commenced with the delivery of a current that slowly increased from 0 mA to 1.5 mA (ramp-up duration of 15 s) and that slowly dropped from 1.5 mA to 0 mA at the end of the stimulation (ramp-down duration of 15 s; Cerruti and Schlaug, 2008 ; Holland et al, 2011 ).…”
Section: Methodsmentioning
confidence: 84%
“…These findings also provide implications for decreasing deception in moral hypocrisy. As previous studies show, great fraction of people show moral hypocrisy [i.e., 90% in Baston et.al.’s Study 2 (C. Daniel Batson et al, 1997 ), 100% in Lönnqvist et al’s Study 1 ( Lönnqvist et al, 2014 ), about 90% in our previous study ( Tang et al, 2017 )]. However, research about how to decrease it is still at the early stage.…”
Section: Discussionmentioning
confidence: 44%
“…Although increasing the concerns of self-image could decrease moral hypocrisy (C Daniel Batson et al, 1999 ; Lönnqvist et al, 2014 ), self-deception was found to be hardly diminished and quickly recovered even after repeatedly presenting the reality to people ( Chance et al, 2015 ). Our previous study found that facilitating prosocial motives could effectively decrease deception in moral hypocrisy ( Tang et al, 2017 ). Results in the current study support this finding by showing that prosocials were less deceptive and hypocritical than proselfs.…”
Section: Discussionmentioning
confidence: 99%